A importância que metalúrgicos e músicos atribuem à audição e sua preservação - Neves, Renata Ribeiro Rodrigues (2007)
Objective: Know the importance that metallurgic workers and musicians attribute to the hearing and its preservation and observe if the information access do implicate a distinguished way to attribute importance to them. We chose twelve subjects, six metallurgic workers and six musicians of rock and roll. Method: Interviews. We utilized as method Content´s Analysis by Bardin (2004). Results: we have the categories: definition of the hearing, loss, protection of the hearing and pleasurable and unpleasurable sounds. The importance of the hearing is present in every category. Metallurgic workers and musicians, attribute high value to the hearing and its preservation. The access to the information do not implicate a distinguished way to attribute importance to the hearing and its preservation, on the contrary shows that the information given, sometimes, do not goes by chance to their reality and questions, is a simple transference of data and do not become knowledge. The musicians have the access of the information and the professional dependence that they present related to the hearing, also make that they attribute a great value to it, in the mean time, the need of a good performance on their presentations seems to be one of the most important factors to the non use of the hearing protection on those moments. Considerations: This directed us to a most humanist view, where is need to valorize a psychosocial reality and to know the subjects doubts, for that, going by chance to their truly wishes, they could be affected to the information, allowing the reflection, the knowledge and stimulate the act of having an idea about